2012
DOI: 10.1111/j.1754-9485.2011.02327.x
|View full text |Cite
|
Sign up to set email alerts
|

High management impact of Ga‐68 DOTATATE (GaTate) PET/CT for imaging neuroendocrine and other somatostatin expressing tumours

Abstract: GaTate PET/CT imaging provides additional diagnostic information in a high proportion of patients with consequent high management impact. GaTate PET/CT could replace (1)In-111 octreotide scintigraphy at centres where it is available given its superior accuracy, faster acquisition and lower radiation exposure. Rapid implementation could be achieved by allowing substitutional funding in the Medicare Benefit Schedule.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
199
2
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(207 citation statements)
references
References 21 publications
5
199
2
1
Order By: Relevance
“…Indeed, such comparative studies also found more foci identified with 68 Ga-based tracers than with SPECT (27,31,32). These studies on average found 30% (27,32,33) more foci using PET than SPECT. Compared with our study in which we found a higher percentage of additional lesions (50%), it seems we could have a better detection rate.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Indeed, such comparative studies also found more foci identified with 68 Ga-based tracers than with SPECT (27,31,32). These studies on average found 30% (27,32,33) more foci using PET than SPECT. Compared with our study in which we found a higher percentage of additional lesions (50%), it seems we could have a better detection rate.…”
Section: Discussionmentioning
confidence: 85%
“…Still, whether 10 or 15 liver metastases are found is not necessarily important additional information. However, also when analyzing organ by organ, 58 additional organ systems were found to be involved in 40 patients when 64 Cu-DOTATATE was used, compared with 111 In-DTPA-OC, which could potentially be of importance for the prognosis (23,24) and treatment selection (25)(26)(27)(28). Nevertheless, more foci found by PET are not necessarily representative of true-positive foci.…”
Section: Discussionmentioning
confidence: 99%
“…Well-differentiated PNETs In octreotide scintigraphy and 68 Ga-DOTA-octreotate PET/CT were used to obtain non-invasive SSTR images, which were useful in identifying well-differentiated PNETs. Poorly differentiated PNETs, on the other hand, exhibited high 18 F-FDG activity [17][18][19][20][21]. It was reported that 18 F-FDG uptake of PNETs was useful for predicting tumor aggressiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Usually, high FDG avidity correlates with poorly differentiated pNETs and increased mortality risk [31,32]. Recently, the use of 68 Ga-labeled somatostatin analogs has been proposed by several authors and shown to be superior to both SRS and conventional cross-sectional imaging [33][34][35][36]. Furthermore, the simultaneous use of PET and CT imaging techniques (PET-CT) has been shown to have a sensitivity ranging from 94 to 100 % [34,37].…”
Section: Tumor Localizationmentioning
confidence: 99%